Psychiatric genetic counselling: current landscape and opinions of psychiatric healthcare professionals in public hospitals in Cape Town, South Africa - Ellis, Lize (Department of Pathology, 2025)
Psychiatric genetic counselling: Current landscape and opinions of psychiatric healthcare professionals in public hospitals in Cape Town, South Africa Psychiatric conditions are common, and psychiatric genetic counselling (PGC) aims to help people understand their, or a family member's, mental illness better, as well as help them understand the factors that can contribute to the development of a mental illness. However, PGC services are not implemented routinely despite reported patient benefits of increased patient empowerment and self-efficacy. This study serves as a pilot project to investigate current practices of mental illness counselling services, focusing on aetiology, provided by psychiatric healthcare professionals at a single unit in the public health sector in Cape Town, South Africa. A pragmatic qualitative research approach, using semi-structured interviews, was used to explore the questions patients ask in terms of recurrence and causes of their mental illness, as well as healthcare provider's (HCPs) opinions on offering a PGC service. Ten interviews were thematically analysed. Results showed that PGC is not being routinely implemented in psychiatric consultations, patients and families have limited genetic knowledge, and family members frequently ask about the mental health condition and its causes. Psychiatric HCPs seemed to believe PGC is likely to be beneficial to the patient, their families and mental health services, and would use such a service if available to them. However, there were several perceived barriers to establishing a PGC service, such as limited resources and available time, which makes a PGC service unfeasible at this point. These results will contribute to the body of knowledge on PGC (such as potential applications, benefits and obstacles, and acceptability of PGC) and may serve as a starting point to considering the implementation of a PGC service in Cape Town, South Africa.